Kualitas Semen Beku Sapi Friesian Holstein Produksi BIB Lembang dengan Lama Waktu Thawing yang Berbeda - Harissatria; Syahro Ali Akbar (Jurnal Peternakan Mahaputra, 2021)
This study aims to determine the effect of thawing time on the quality of frozen semen of Friesian Holstein cattle produced by BIB Lembang which is stored in UPTD Puskeswan Padang Panjang. This study used an experimental method with a completely randomized design (CRD). Consists of 3 treatments, namely thawing time of 1 second, 10 seconds and 20 seconds at 38°C and each treatment was repeated 5 times. The material used in this study was 15 straws of frozen semen from FH cattle produced by BIB Lembang with the same bull code. This research was conducted at the Laboratory of Animal Biotechnology, Andalas University Padang. The results showed that the thawing duration of 1 second, 10 seconds and 20 seconds gave no significant difference (P> 0.05) to the percentage of life, percentage of motility and percentage of abnormalities in frozen semen of FH cows thawed at 38ºC. Based on the research results, it can be concluded that frozen semen from FH cattle produced by BIB Lembang, thawed at 38ºC for 1 second, 10 seconds and 20 seconds is still suitable for IB.